Design of spectrally efficient ultra-wideband waveforms using Hermite–Rodriguez functions - Yusoff, Mohd Amaluddin; Zang, Zhuquan; Abeysekera, S. (The Institution of Engineering and Technology, 2012)
Spectral efficiency is a major requirement in ultra-wideband (UWB) communication systems because of very low power spectral density (PSD) regulations imposed on the transmitted signals. Besides, large number of orthogonal waveforms is highly desirable in multiuser systems. In this study, the design of a set of spectrally efficient orthogonal waveforms is investigated. The design of UWB waveforms based on orthogonal Hermite–Rodriguez basis functions and linear frequency modulation (LFM) is proposed herein. The design is formulated as a quadratic semi-infinite programming problem with spectral and orthogonality constraints. Numerical examples are presented to illustrate the effectiveness of Hermite–Rodriguez based waveforms with the proposed optimisation approach. Comparison with a recent result shows that the proposed approach compares favourably with those reported in the literatures in terms of the number of waveforms can be produced and the achievable spectral efficiency of the designed waveforms.